Intention of COVID-19 Vaccination in the Sri Lankan Context: A structural equation model approach - Ahamed Rifath; Fathima Jemziya (ACHSM, 2022)
Introduction: The intention on vaccination of COVID-19 is influenced by demographic and psychological factors. An understanding of the factors that influence the intention of COVID-19 vaccination is important to achieve the successful vaccination programs. Objective: The objective of this study is to determine the critical factors affecting the intention of COVID-19 vaccination in Sri Lanka. Methodology: An online questionnaire was implemented amongst Sri Lankans to acquire the primary data. The questionnaire assessed the social demographic features, vaccination details, perception and intention about the vaccination, social norm, media exposure, and trust towards vaccines. Descriptive analysis was used to analyse the demographic characters and vaccination details. The structural equation model was used to analyse the relationship between the intention of COVID-19 vaccination and other relevant factors. Results: The results showed that the perception of vaccine, social norms and trust were significantly related with people's intention towards vaccination, whereas media exposure showed an insignificant relationship with the intention towards vaccination. Meanwhile, perception about vaccine and media exposure had significant relationships between trust of the vaccines. Conclusion: It was conclusive that the intention of the COVID-19 vaccination was greatly influenced by the perception of vaccine, social norms and trust besides media exposure, which had an indirect effect on intention towards vaccination of COVID-19.